Biomarker characterization of the North Water Polynya, Baffin Bay: implications for local sea ice and temperature proxies - D. J. Harning; B. Holman; L. Woelders; A. E. Jennings; J. Sepúlveda; J. Sepúlveda (Biogeosciences, 2023)
The North Water Polynya (NOW, Inuktitut: Sarvarjuaq; Kalaallisut: Pikialasorsuaq), Baffin Bay, is the largest polynya and one of the most productive regions in the Arctic. This area of thin to absent sea ice is a critical moisture source for local ice sheet sustenance and, coupled with the inflow of nutrient-rich Arctic Surface Water, supports a diverse community of Arctic fauna and indigenous people. Although paleoceanographic records provide important insight into the NOW's past behavior, it is critical that we better understand the modern functionality of paleoceanographic proxies. In this study, we analyzed lipid biomarkers, including algal highly branched isoprenoids and sterols for sea ice extent and pelagic productivity and archaeal glycerol dibiphytanyl glycerol tetraethers (GDGTs) for ocean temperature, in a set of modern surface sediment samples from within and around the NOW. In conjunction with previously published datasets, our results show that all highly branched isoprenoids exhibit strong correlations with each other and not with sterols, which suggests a spring or autumn sea ice diatom source for all highly branched isoprenoids (HBIs) rather than a combination of sea ice and open-water diatoms as seen elsewhere in the Arctic. Sterols are also highly concentrated in the NOW and exhibit statistically higher concentrations here compared to sites south of the NOW, consistent with the order of magnitude higher primary productivity observed within the NOW relative to surrounding waters in spring and summer months. Finally, our local temperature calibrations for GDGTs and OH-GDGTs reduce the uncertainty present in global temperature calibrations but also identify some additional variables that may be important in controlling their local distribution, such as nitrate availability and dissolved oxygen. Collectively, our analyses provide new insight into the utility of these lipid biomarker proxies in high-latitude settings and will help provide a refined perspective on the past development of the NOW with their application in downcore reconstructions.